Cardiac tumours simulating collagen vascular disease. - Fitzpatrick, A P (1986)
Cardiac tumours can mimic collagen vascular disease and they are often accompanied by profound systemic upset. Both benign and malignant tumours may present in this way. Three cases of cardiac tumour, two malignant and one benign, are reported with just such a presentation. A review of fifteen similar case reports showed that a spectrum of different collagen vascular diseases was diagnosed and treated before the true diagnosis emerged. In half of these cases the cardiac tumour was only diagnosed at necropsy. The diagnosis of collagen vascular disease should not be made in the absence of corroborative laboratory data. In cases of malignant cardiac tumour, and less commonly with atrial myxoma, M mode and cross sectional echocardiography may not exclude the diagnosis. There may be a good response to steroid treatment in cases of suspected but not confirmed collagen vascular disease in which the true diagnosis is cardiac tumour.